Investigating the opinions on telephonic advanced maternal age genetic counselling - Bayley, Samantha (Department of Pathology, 2024)
Background: The research on telephonic genetic counselling (GC) services has increased since 2020. However, there is still limited research on the experience and opinions of this service from the patients' perspective. This is particularly true in low to middle-income settings such as South Africa. The advanced maternal age (AMA) telephonic GC service at Groote Schuur Hospital (GSH), has been implemented since COVID-19 regulations were enforced in 2020. This study aims to investigate the opinions and experiences of the patients on this telephonic service. Methods: This qualitative study used individual semi-structured interviews, both in-person and telephonic, and followed a phenomenological approach. The data were analysed using thematic data analysis. Results: The participants (n=9) had varying opinions about the telephonic GC service offered through GSH. The information gathering process varied for the participants; especially the differing Midwife Obstetric Units (MOUs) referrals and the information given. Some participants found online resources helpful, but not all participants felt the same. Overall, the participants felt the information given by the GC service was informative and useful. An important outcome of the research was a general trust between the GC trainee and participants but a distrust between other health care professionals and the participants. Numerous factors influenced decision-making concerning invasive testing including participants' fears and seeking control or having a sense of control based on if you would cope with having a child with DS. Conclusion: The distrust in the healthcare system can have a significant impact on patients' understanding and decision-making in a GC session. Overall, there are benefits and barriers to be aware of, but most participants found the GC session informative and allowed them to make informed decisions. This research included a limited sample size, which prevents the generalizability of these findings.